Cardioplegia practice in paediatric cardiac surgery: a UK & Ireland survey. (March 2019) - Drury, Nigel E.; Horsburgh, Angela; Bi, Rehana; Willetts, Robert G.; Jones, Timothy J.
Introduction: Many techniques are available for cardioplegic arrest in children, but there is a lack of late phase clinical trials to guide practice. We surveyed paediatric cardiac surgeons and perfusionists to establish current practice and willingness to change within a clinical trial. Methods: An online survey was sent to all consultant paediatric cardiac surgeons and chief perfusionists in paediatric centres in the UK and Ireland. Information was sought on cardioplegia type, composition, temperature, topical cooling, dosing for induction and maintenance, interval between doses, whether practice changed with patient age or complexity and whether respondents would be willing and able to use different cardioplegia solutions within a randomised trial. Results: Responses were obtained from 32 (78.0%) surgeons and 12 (100%) perfusionists. Twenty-seven (84.4%) surgeons use blood cardioplegia in infants, with St. Thomas' Harefield preparation the most popular (19, 59.4%), used routinely in eight (66.7%) centres. Twenty-two (68.8%) administer at 4-6°C, 18 (56.3%) use topical cooling, 18 (56.3%) give 30 ml/kg induction and 15 ml/kg maintenance, with 23 (71.9%) re-dosing every 20-25 minutes. Thirty (93.8%) surgeons were open to randomising patients in a trial, with del Nido (29, 90.6%) the most popular. Conclusions: This survey demonstrates heterogeneity in cardioplegia practice. Whilst most surgeons use blood cardioplegia, there is variation in type, temperature, topical cooling, dosing and intervals. Combined with a lack of evidence from late phase trials, our findings support the presence of clinical equipoise. Surgeons are willing to change practice, suggesting that a pragmatic, multi-centre, randomised, controlled trial of cardioplegia in children is feasible.